The Role of Islamic Religious Education in Shaping Student Character Amid the Moral Crisis of the Modern Era - Amin, Miftakhul (Multidiscience : Journal of Multidisciplinary Science, 2025)
This study aims to analyze the role of Islamic Religious Education (PAI) in shaping student character amid the moral crisis of the modern era. Technological advancement, the global flow of information, and shifts in social values have triggered a moral crisis marked by increasing juvenile delinquency, drug abuse, promiscuity, and the emergence of LGBT trends among students. In this context, PAI serves a strategic function as a moral and spiritual foundation that fosters religious and ethical character. This research employs a descriptive qualitative approach through literature review and document analysis to evaluate the effectiveness of PAI in instilling core character values such as integrity, responsibility, empathy, religiosity, and discipline. The findings indicate that PAI is effective in shaping student character when supported by a contextual curriculum, competent educators, innovative teaching methods, and active involvement from parents and the community. The study also highlights the need for transformative PAI learning approaches, including religious digital literacy, experiential learning, and continuous teacher training. These insights are expected to contribute to the development of a more relevant and responsive PAI curriculum in addressing the moral challenges of the modern era.